PENGARUH FAKTOR INTERN DAN EKSTERN TERHADAP TINGKAT ADOPSI INOVASI TEKNOLOGI USAHA TANI NANAS DI KECAMATAN DENDANG KABUPATEN TANJUNG JABUNG TIMUR - Mitaria, Mitaria; Rosyani, Rosyani; Muchlis, Fuad (Agros Journal of Agriculture Science, 2024)
This research aims to; 1) understand the picture of pineapple farming development. 2) determine the level of adoption of technological innovation in pineapple farming, and 3) analyze the influence of internal and external factors on the adoption of technological innovation in pineapple farming in Dendang District, East Tanjung Jabung Regency. This research analysis uses SEM-PLS data processing techniques. Research result; (1) An overview of the development of pineapple farming in Dendang District, which has begun to be declared as a superior horticultural product in East Tanjung Jabung Regency since 2019, the development of pineapple farming is a program for developing agricultural facilities and infrastructure, (2) The level of adoption of pineapple farming technology innovation in Dendang District is in the high category and (3) Results of analysis of the influence of internal factors on farming, the influence of factor X2 on Y2, the influence of factor X2 on Y2, the influence of X1 on Y2 through Y1 and the influence of, however, the direct influence of X1 on Y2 and the indirect influence of X2 on Y2 through Y1 with a p-value > 0.05 have no significant effect.